Adapting Culinary Business Model as a Source of Teaching Material in Hospitality Business Course - Masri Ridwan; Muhadjir Suni; Muh. Taufik S (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to describe the strategy of culinary business adaptation and integration of culinary business adaptation into the teaching materials of hospitality business study programs in the city of Pare-Pare during the covid-19 pandemic. This research uses a qualitative approach of this type of case study, Researchers sought to uncover the reality of the meaning that occurred in the field about the form of culinary business adaptation in the city of Pare-Pare during the covid-19 pandemic as material for medical business courses (BHO). In this case, the researcher conducts interviews, observations and documentation to get information about the main theme of studies. The analysis of the data is carried out circularly, starting from the presentation of data, reduction of data and conclusions. The results of his research are: 1) Social commitment characterized by new activities and ways of life that refer to "happy business, happy worker, happy customer"; 2) Innovation of business digitization one of them is switching to non-cash transactions, making online sales, the emergence of creativity and innovation in the use of technology to raise the value of kuline products 3) The development of culinary business in the city of Pare-pare can be used as one of the references for the source of hospitality business teaching materials.  This research also provides a recommendation in writing a teaching book about the management of culinary businesses in the city of Pare-Pare as a guideline for the development of creative economy-based businesses in optimizing business potential in the New Normal Period.